2022
DOI: 10.1038/s41467-022-34125-8
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of ansamers in the synthesis of cyclic peptides

Abstract: Abstractα-Amanitin is a bicyclic octapeptide composed of a macrolactam with a tryptathionine cross-link forming a handle. Previously, the occurrence of isomers of amanitin, termed atropisomers has been postulated. Although the total synthesis of α-amanitin has been accomplished this aspect still remains unsolved. We perform the synthesis of amanitin analogs, accompanied by in-depth spectroscopic, crystallographic and molecular dynamics studies. The data unambiguously confirms the synthesis of two amatoxin-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…The conformation of α-amanitin and P ansa -amanullin is stabilized by a hydrogen bond between the amide hydrogen of Gly5 and the backbone carbonylgroup of Asn1 (Figure 1.c). 29 This hydrogen bond is also found in the crystal structures of other amatoxins. 44 To investigate the effects of the loss of this hydrogen bond on the structure and conformational stability, we synthesized a derivative with the N-methylated amino acid sarcosine (three-letter code: Sar) instead of glycine 5 (Figure 1.b).…”
Section: Gly5sar-amanullinmentioning
confidence: 53%
See 4 more Smart Citations
“…The conformation of α-amanitin and P ansa -amanullin is stabilized by a hydrogen bond between the amide hydrogen of Gly5 and the backbone carbonylgroup of Asn1 (Figure 1.c). 29 This hydrogen bond is also found in the crystal structures of other amatoxins. 44 To investigate the effects of the loss of this hydrogen bond on the structure and conformational stability, we synthesized a derivative with the N-methylated amino acid sarcosine (three-letter code: Sar) instead of glycine 5 (Figure 1.b).…”
Section: Gly5sar-amanullinmentioning
confidence: 53%
“…For amatoxins, this ring is the peptide ring (macrolactam), where the direction is defined by the sequence N → C α → carbonyl-C. Because of this directionality, the main ring has two distinct sides, and the position of the second cycle with respect to the main ring defines two distinct isomers. In our previous study, 29 we suggested the term ansamers for this type of isomerism, with P -ansamer denoting one option and M -ansamer the other. To assign the stereochemical descriptor (M or P configuration), the CIP (Cahn-Ingold-Prelog) rules can be followed.…”
Section: Gly5sar-amanullinmentioning
confidence: 99%
See 3 more Smart Citations